2019
DOI: 10.2147/opth.s198349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of short-term oral vitamin A supplementation on the ocular tear film in patients with dry eye</p>

Abstract: Objective: To investigate the effects of short-term oral vitamin A supplementation on the ocular tear film in patients with dry eye. Methods: In total, 30 male patients with dry eye (age range, 18-38 years; mean age, 25.2±2.8 years) who did not wear contact lenses or exhibit any ocular (other than dry eye) or systemic diseases were included, along with 30 age-matched men (control group; mean age, 24.5±2.3 years) with healthy eyes. Subject exclusion was based on the findings of the McMonnies questionnaire (cuto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
(51 reference statements)
2
28
0
1
Order By: Relevance
“…103 Other vitamins involved in ocular surface health are vitamins A and D used as oral supplements and vitamin A as a topical application, which have demonstrated an improvement in DED signs and symptoms. [104][105][106][107] Amino acid-enriched tear substitutes have been proven to be effective in improving corneal nerve structure in patients with DED. 108 Possible future developments will consider the use of biological drugs in the treatment of DED and associated conditions such as psoriasis.…”
Section: Nerve Treatmentmentioning
confidence: 99%
“…103 Other vitamins involved in ocular surface health are vitamins A and D used as oral supplements and vitamin A as a topical application, which have demonstrated an improvement in DED signs and symptoms. [104][105][106][107] Amino acid-enriched tear substitutes have been proven to be effective in improving corneal nerve structure in patients with DED. 108 Possible future developments will consider the use of biological drugs in the treatment of DED and associated conditions such as psoriasis.…”
Section: Nerve Treatmentmentioning
confidence: 99%
“…This is associated with a reversal of the process of squamous metaplasia, as documented by conjunctival impression cytology [75]. Furthermore, a recent clinical study has shown that short-term vitamin A supplementation in patients with DED improves the quality of tears [78].…”
Section: Vitamin Amentioning
confidence: 99%
“…the ocular surface disease index, OSDI) [17]. Several diagnostic tests have been used to the assess eye dryness in terms of the quality and quantity of tears [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%